Professors, share your views for a better world - Abdul Hamid, Zakri (New Straits Times, 2011)
THE newly formed National Professors Council (MPN) will, at its first congress on July 6- and 7, reaffirm its commitment to building a knowledge-based society and support the 1Malaysia concept, the New Economic Model, Government Transformation Plan and Economic Transformation Plan.